Gastroretentive Pulsatile Release Tablets of Lercanidipine HCl: Development, Statistical Optimization, and In Vitro and In Vivo Evaluation - Gagganapalli Santhoshi Reddy; Usha Yogendra Nayak; Praful Balavant Deshpande; Srinivas Mutalik (The Scientific World Journal)
The present study was aimed at the development of gastroretentive floating pulsatile release tablets (FPRTs) of lercanidipine HCl to enhance the bioavailability and treat early morning surge in blood pressure. Immediate release core tablets containing lercanidipine HCl were prepared and optimized core tablets were compression-coated using buoyant layer containing polyethylene oxide (PEO) WSR coagulant, sodium bicarbonate, and directly compressible lactose. FPRTs were evaluated for various in vitro physicochemical parameters, drug-excipient compatibility, buoyancy, swelling, and release studies. The optimized FPRTs were tested in vivo in New Zealand white rabbits for buoyancy and pharmacokinetics. DoE optimization of data revealed FPRTs containing PEO (20% w/w) with coat weight 480 mg were promising systems exhibiting good floating behavior and lag time in drug release. Abdominal X-ray imaging of rabbits after oral administration of the tablets, confirmed the floating behavior and lag time. A quadratic model was suggested for release at 7th and 12th h and a linear model was suggested for release lag time. The FPRT formulation improved pharmacokinetic parameters compared to immediate release tablet formulation in terms of extent of absorption in rabbits. As the formulation showed delay in drug release both in vitro and in vivo, nighttime administration could be beneficial to reduce the cardiovascular complications due to early morning surge in blood pressure.